The Implementation of Teacherpreneurship of PGMI Students INISNU Temanggung - Andrian Gandi Wijanarko; Iis Narahmalia (Al-Aulad: Journal of Islamic Primary Education, 2022)
This actian research discusses the practice of teacherpreneurship among INISNU Temanggung students. This research uses a service learning approach. The research carried out observation, planning, action, and evaluation regarding the making of NIB (Business License Number). The population of this research is 24 students of the PGMI INISNU Temanggung study program. In the initial ownership of NIB, only 2 college students (8.3%) already had it, after taking action there was an increase to 23 college students (95.8%). The implementation of teacherpreneurship practices is not limited to the creation of a product, but students are equipped with the principles and mentality to become a competitive entrepreneur. Students are able to produce works in the form of entrepreneurial profiles, teacherpreneurship products, NIB, and practice teacherpreneurship in Selopampang, Temanggung Regency. The impact of this research is that students have a mentality in entrepreneurship. Students are very active when involved in determining the direction of this research, both in the training process, production stages, to determining post-production strategies. In addition, lecturers and students are able to take transformative action by having the same understanding that the activities carried out for PGMI INISNU Temanggung students.